An integrated ecological and cultural framework for landscape sensitivity assessment in Cyprus. (March 2020) - Manolaki, P.; Zotos, S.; Vogiatzakis, I.N.
Highlights: Integrated landscape sensitivity assessment can capture Mediterranean complexity. In islands the ecological and cultural sensitivity are inextricably linked. The importance of natural and cultural features in a landscape is scale dependent. Fine scale landscape mapping is suitable for Local Development Plans. Abstract: The aim of the paper is to describe the development and implementation of an integrated framework for landscape sensitivity assessment in Cyprus, a biodiversity hotspot with high landscape diversity. Akamas peninsula, the western tip of the island covering an area of 230 km 2, is under great pressure for development, notwithstanding it hosts 21 terrestrial habitats, four of which are priority at European level, in addition to 48 endangered plant species. Following previous coarse scale landscape mapping on the island, a more detailed landscape map at 1:10, 000 scale (Level III) was produced, appropriate for local planning purposes. Overall landscape sensitivity was evaluated as a function of ecological, cultural and visual sensitivity of the study area. 66 Land Description Units (LDUs) were mapped and 38 Landscape Types (LCTs) were identified for the Akamas peninsula. Ecological sensitivity assessment for Akamas determined that 85 % of the LDUs have high to very high sensitivity with those within Natura 2000 sites having the highest. Out of 66 LDUs, 35 % were of high or moderate cultural sensitivity and there were 32 LDUs with high overall landscape sensitivity i.e. when visual sensitivity was also considered. Based on the various degrees of sensitivity identified in this study, the task of policy makers is to establish a policy response for each landscape type based on the principles and practice of sustainability. In the Mediterranean, the development of an integrated assessment for landscape sensitivity is critically important at a time of rapid change.